2021
DOI: 10.26508/lsa.202000790
|View full text |Cite
|
Sign up to set email alerts
|

PNKP is required for maintaining the integrity of progenitor cell populations in adult mice

Abstract: DNA repair proteins are critical to the maintenance of genomic integrity. Specific types of genotoxic factors, including reactive oxygen species generated during normal cellular metabolism or as a result of exposure to exogenous oxidative agents, frequently leads to “ragged” single-strand DNA breaks. The latter exhibits abnormal free DNA ends containing either a 5′-hydroxyl or 3′-phosphate requiring correction by the dual function enzyme, polynucleotide kinase phosphatase (PNKP), before DNA polymerase and liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…We expand the phenotype of PNKP variants with lissencephaly, which has not been previously reported to our knowledge. It was found that PNKP knockout mice had significantly reduced doublecortin +ve (DCX+ve) neuroblasts in the dorsolateral horn, with PNKP deficiency disrupting neural stem cell maintenance 43 . Doublecortin (encoded by DCX gene) interacts with platelet‐activating factor acetylhydrolase (encoded by LIS1 gene), and both are essential to maintain microtubule function for neuronal migration in the developing cerebral cortex 44 which may explain the lissencephaly phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…We expand the phenotype of PNKP variants with lissencephaly, which has not been previously reported to our knowledge. It was found that PNKP knockout mice had significantly reduced doublecortin +ve (DCX+ve) neuroblasts in the dorsolateral horn, with PNKP deficiency disrupting neural stem cell maintenance 43 . Doublecortin (encoded by DCX gene) interacts with platelet‐activating factor acetylhydrolase (encoded by LIS1 gene), and both are essential to maintain microtubule function for neuronal migration in the developing cerebral cortex 44 which may explain the lissencephaly phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, loss of Pnkp proved to be more severe when compared to Lig4 or Xrcc1 loss, indicating that at least in mice, Pnkp may be involved in the repair of a wider range of lesions, demonstrating an important difference between PNKP function in human and mouse ( Shimada et al, 2015 ). In general, Pnkp loss has been shown to induce a thinning in the cerebral cortex, abundant p53-dependent apoptosis and impaired NPCs proliferation, leading to microcephaly ( Shimada et al, 2015 ; Shin et al, 2021 ).…”
Section: Microcephaly Associated With Dna Damagementioning
confidence: 99%
“…Moreover, in the PNKP KO mice adult is strongly impaired in neurogenesis and subventricular zones (SVZ) cell population. Especially, PNKP deletion affects a rapid inhibition of cell proliferation and self-renewal in neural progenitor cells (Shin et al 2021).…”
Section: Detection Of Novel Genes On Recessive Heterozygous Alleles I...mentioning
confidence: 99%